Factors related to delay in cervical cancer diagnosis and treatment among women in Bangladesh: A cross-sectional study - Hoque, Md Moinul; Nahar, Nasreen; Mahbub, Md Shahriar; Akter, Jesmin; Ara, Begum Rowshan (Journal of Biomedical Sciences, 2023)
Background: Bangladesh has a large proportion of women at risk of developing cervical cancer. Though it is considered preventable, it is the second commonest cancer of women in Bangladesh. This study explored the factors influencing the delays in seeking cervical cancer care. Material and methods: Three hundred and ninety nine (399) randomly selected women with cervical cancer attending clinical care in a tertiary hospital were enrolled. Both quantitative and qualitative methods were followed. Face-to-face interviews using a semi-structured and in-depth questionnaire were carried out. The univariate analysis measured the association with statistical significance set at p<0.05. Content and context analyses were performed for a qualitative segment of the study. Results: The mean age of the respondent was 54.3 years (Mean ± SD, 54.3±11.7). The median duration of primary, secondary and tertiary delays was 45, 45 and 60, respectively. The association between primary delay and personal factors, e.g., lack of knowledge, was statistically significant (p<0.05). Economic factors were closely associated with secondary delay (p=0.000). Issues like healthcare facilities were significant for tertiary delay (p=0.000). Conclusion: This study identified multiple factors that can be addressed to reduce delays regarding cervical cancer diagnosis and treatment. Steps to reduce these delays can be expected to improve clinical care and the outcome of this cancer in women in Bangladesh.